If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3n + 3) = 39 Reorder the terms: 3(3 + 3n) = 39 (3 * 3 + 3n * 3) = 39 (9 + 9n) = 39 Solving 9 + 9n = 39 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 9n = 39 + -9 Combine like terms: 9 + -9 = 0 0 + 9n = 39 + -9 9n = 39 + -9 Combine like terms: 39 + -9 = 30 9n = 30 Divide each side by '9'. n = 3.333333333 Simplifying n = 3.333333333
| Have-6+7h=42 | | y=3x-5-16 | | 2y-27=299 | | -2x-3x+2.5=10 | | 5+11x=-55 | | +13y-8y= | | 4x-7=38 | | 21+8x+(-15)= | | 0.72-2x=2x+x | | -0.25c+20.5=12.9 | | E/9-5=-11 | | 8x-2-4x=-12 | | E/9-5=-5 | | 5x/3+3=x+7 | | -0.25c+20.5= | | 1.5(9b-27)=36 | | 1=y(4x+1) | | 0.20+0.35(50)=31.5 | | 2x+1=13-x | | -4(2t+7)=-44 | | 2x-7y=11fory | | 4x+7=-4x+20 | | -12x+12x+8=16 | | T-15=76 | | 6y+-15=9 | | 7=-7-(p-8) | | 8x+0.5=7x+2 | | 2m+13=25 | | 19m+9n=16 | | 2x+4=4x+16 | | 5x+12=-42-4x | | 9=q-4 |